2014
DOI: 10.1039/c4cp00840e
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of hydration water in a model peptide

Abstract: The molecular dynamics of aqueous solutions of a model amphiphilic peptide is studied as a function of concentration by broad-band light scattering experiments. Similarly to protein aqueous solutions, a considerable retardation, of about a factor 6-8, of hydration water dynamics with respect to bulk water is found, showing a slight dependence on solute concentration. Conversely, the average number of water molecules perturbed by the presence of peptide, i.e. the hydration number, appears to be strongly modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 50 publications
(108 reference statements)
5
36
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12]21 The formation of strong H-bonds, which disrupts the water structure and avoids synergistic water molecule reorientation in the immediate vicinity of the peptide, is responsible for the slowdown of water motion. [5][6][7][8][9][10][11][12]21 The formation of strong H-bonds, which disrupts the water structure and avoids synergistic water molecule reorientation in the immediate vicinity of the peptide, is responsible for the slowdown of water motion.…”
Section: View Article Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12]21 The formation of strong H-bonds, which disrupts the water structure and avoids synergistic water molecule reorientation in the immediate vicinity of the peptide, is responsible for the slowdown of water motion. [5][6][7][8][9][10][11][12]21 The formation of strong H-bonds, which disrupts the water structure and avoids synergistic water molecule reorientation in the immediate vicinity of the peptide, is responsible for the slowdown of water motion.…”
Section: View Article Onlinementioning
confidence: 99%
“…All these features are in accordance with many pieces of experimental evidence and many molecular dynamic studies, which suggested a small number of water molecules coordinated to acceptor and donor groups of peptides. [5][6][7][8][9][10][11][12]21 The formation of strong H-bonds, which disrupts the water structure and avoids synergistic water molecule reorientation in the immediate vicinity of the peptide, is responsible for the slowdown of water motion.…”
Section: Chemical Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] From the experimental point of view,t here is no exhaustive experimental technique that directly probess pecific biomolecule-water interactions in solution, sincec hanges in geometricala rrangement are too fast, on the picosecondt imescale. [13] Nevertheless, neutron scattering, [14] NMR, [15,16] terahertz, [17][18][19] dielectric relaxation, [20] and fluorescence [21] spectroscopy has shownt hat molecular reorientation occurs more slowly than in bulk water,m ainly because of the peptide-water H-bonds and the topologically het-erogeneous nature of ap eptide surface, which disrupts the synergistic water-water reorientation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The bio-functionality of a protein is directly linked to the amino acid sequence and structure that characterizes the native protein state; furthermore, it is strongly dependent on the solvent, i.e., water, which actually functions as an amino acid [4]. Dry proteins exhibit no biological activity and require at least a water monolayer (a first hydration shell) covering their surface to function as proteins [5][6][7]. Water in the form of internal water is also an essential part of the three-dimensional structure of a protein [8,9].…”
Section: Introductionmentioning
confidence: 99%